Precarization or protection? The impact of trade and labour policies on informality - Rita Almeida; Lourenço Senne Paz; Jennifer P. Poole (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Several episodes of market-oriented reforms in developing countries have been accompanied by a significant rise in work outside of the formal economy. This paper investigates whether the impact of increased exposure to trade on formal employment is mediated by the strength of labour regulations. We rely on data from the Brazilian Census which provides information on workers' demographics and employment, including job formality status. Our estimation strategy exploits quasi-exogenous changes in industry-level real exchange rates to explore the likelihood of informality across employers exposed to varying degrees of de facto labour regulations. To instrument for labour enforcement, we utilize two key features of Brazilian labour institutions-budgetary decisions about the availability of resources occur at the federal level, while decisions about where to inspect occur at the local level. Our instrumental variables results suggest that strict labour regulations may lead to a precarization of employment, rather than offering protection for workers.
Keywords: C26; F16; J46; J80; 330; Brazil; enforcement; informality; trade; labour regulations; instrumental variables